Quantum Physics Lecture Profile in Supporting Student Computation Thinking (CT) Integration Program - Riskawati Riskawati; Dadi Rusdiana; Hendra B (Universitas Sultan Ageng Tirtayasa, 2024)
The purpose of this study is to describe how the profile of lecture needs related to content in quantum physics at the UNTIRTA Physics Education Study Program. The methods used in this field study are: 1) paper, in the form of curriculum documents, national curriculum and RPS; 2) person, lecturer in quantum physics; 3) the place is located in the Department of Physics FMIPA UNTIRTA. Data collection techniques in field study activities are carried out using non-test instruments carried out through document analysis, questionnaires, interviews and tests. The results of the analysis show that the curriculum of the Quantum Physics Study Program (compulsory) in semester V has not been well developed and is not specifically designed to consider students' deep conceptual understanding, the assessment system has not been able to appropriately follow the 21st century learning system, and learning has not been student-centered. Therefore, an analysis is needed based on the needs of a more in-depth study program to determine the topic of study materials in the Quantum Physics course if it is to be applied in the curriculum.